2006
DOI: 10.1111/j.1520-037x.2006.05408.x
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Aerobic Exercise on Brachial Artery Endothelial Function in Renal Transplant Recipients

Abstract: This study compared the effect of a 30‐minute walk on brachial artery endothelial vasodilatation in kidney transplant (KT) recipients and healthy controls (HCs). Endothelial‐dependent vasodilatation was measured by ultrasound before and after exercise. The HCs experienced a significant increase in vasodilatation after exercise 1 minute postocclusion when compared with the KT recipients (22%±13% vs 3%±4%; V<.05). Also, the HCs had a significantly higher vasodilatation from pretreadmill walk to post‐treadmill wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
3
19
0
2
Order By: Relevance
“…As the results of this study indicate, when the blood pressure increase is prevented in a controlled limb, FMD in that limb increases in both SED and ET subjects. This response is similar to what is observed in subjects following low- to moderate-intensity aerobic exercise (4, 13, 22), during which systolic blood pressure does not significantly increase. Together, these findings suggest that a circulating, pro-dilatory factor may be present, and its effects are dampened by the increased barostress on the blood vessels which occurs during weight lifting.…”
Section: Resultssupporting
confidence: 87%
“…As the results of this study indicate, when the blood pressure increase is prevented in a controlled limb, FMD in that limb increases in both SED and ET subjects. This response is similar to what is observed in subjects following low- to moderate-intensity aerobic exercise (4, 13, 22), during which systolic blood pressure does not significantly increase. Together, these findings suggest that a circulating, pro-dilatory factor may be present, and its effects are dampened by the increased barostress on the blood vessels which occurs during weight lifting.…”
Section: Resultssupporting
confidence: 87%
“…Many studies showed that aerobic training is a strong inducer of NO production, as the exercise increases blood flow and the shear stress acts as an intense stimulus on the endothelium. 57,58 As stated earlier, as the levels of insulin were not different between trained and untrained diabetic rats in our experiments, it is suggested that there was no interference of endogenous insulin concentrations on NO production in these animals. In summary, aerobic training during eight weeks had beneficial effects over the metabolic profile of DM rats, with better glycemic control, weight increase, associated to a reduction of albuminuria and TBARS, amelioration of the kidney's function and NO production, and absence of renal lesions.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to these reports, sustained increase of FMD after acute exercise was observed in postmenopausal women [25]. Regarding healthy controls, Cosio-Lima et al showed acute vasodilatory response after 30-minute walk, comparing FMD between healthy controls and kidney transplant recipients [26]. In a recent study of Llewellyn et al, some interesting findings were reported [29].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the abundance of evidence regarding the chronic effect of exercise on FMD, the impact of acute exercise is still inconclusive. Several researchers have reported reduction of FMD immediately after exercise [22-24], while others have reported improvement [25,26]. Utilization of acute exercise model is advantageous for prescription of appropriate exercise protocol for patients, experimental control of confounding variables, and investigation of mechanisms of acute exercise response [27].…”
Section: Introductionmentioning
confidence: 99%